2004
DOI: 10.1079/pns2003317
|View full text |Cite
|
Sign up to set email alerts
|

Enteral feeding: the effect on faecal output, the faecal microflora and SCFA concentrations

Abstract: Enteral tube feeding is common in both the hospital and community environment; however, patients can suffer alterations in faecal output that can have serious clinical sequelae. Problems associated with accurate characterisation of faecal output and definition of diarrhoea impede the comparison of research studies and prevent standardised assessment of therapeutic interventions in clinical practice. The colonic microflora may protect the patient against diarrhoea by preventing enteropathogenic infection and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 72 publications
0
27
0
5
Order By: Relevance
“…In view of their potential role in the pathogenesis of diarrhoea during ETF a number of studies have investigated the impact of enteral formula on the colonic microbiota of healthy subjects and of patients receiving ETF (Whelan et al 2004a). However, many of these early studies report conflicting results, perhaps as a result of major methodological weaknesses, including small sample sizes, the additional use of enemas or laxatives and the reliance on traditional bacterial culture (Winitz et al 1970;Attebery et al 1972;Bornside & Cohn, 1975).…”
Section: Enteral Tube Feeding and The Colonic Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…In view of their potential role in the pathogenesis of diarrhoea during ETF a number of studies have investigated the impact of enteral formula on the colonic microbiota of healthy subjects and of patients receiving ETF (Whelan et al 2004a). However, many of these early studies report conflicting results, perhaps as a result of major methodological weaknesses, including small sample sizes, the additional use of enemas or laxatives and the reliance on traditional bacterial culture (Winitz et al 1970;Attebery et al 1972;Bornside & Cohn, 1975).…”
Section: Enteral Tube Feeding and The Colonic Microbiotamentioning
confidence: 99%
“…receiving ETF (Whelan et al 2004a). Consumption of an enteral formula supplemented with FOS (10 g/l) was shown to result in an increase in faecal bifidobacteria in nine healthy subjects (Garleb et al 1996).…”
Section: Reduction In Phmentioning
confidence: 99%
“…Oligofructose and inulin stimulate growth and activity of bifidobacteria and lactobacilli without inducing similar changes in anaerobes, clostridia, coliform flora, and the genus Bacteroides [62,63]. Oligofructose partially prevents the decrease of intestinal short-chain fatty acids in subjects on enteral nutrition [64].…”
Section: Prebioticsmentioning
confidence: 99%
“…Due to the lack of a standardized definition, especially in earlier studies, the reported incidences of diarrhoea vary over a very wide range from 2 to 95% [38]. Diarrhoea is, however, a significant problem in intensive care patients which interferes with the adequacy of enteral nutrition [39].…”
Section: Diarrhoeamentioning
confidence: 99%